2000
DOI: 10.1182/blood.v96.9.2973.h8002973_2973_2980
|View full text |Cite
|
Sign up to set email alerts
|

T-lymphocyte production of macrophage inflammatory protein-1α is critical to the recruitment of CD8+ T cells to the liver, lung, and spleen during graft-versus-host disease

Abstract: To investigate the mechanism by which macrophage inflammatory protein-1α (MIP-1α) affects graft-versus-host disease (GVHD), the expression and function of MIP-1α in 2 murine models of GVHD were evaluated. In irradiated class I and class II disparate recipients, the expression of messenger RNA (mRNA) and protein for MIP-1α was significantly increased in GVHD target organs after transfer of allogeneic lymphocytes compared to syngeneic lymphocytes. When lymphocytes unable to make MIP-1α were transferred, there wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 52 publications
2
44
0
Order By: Relevance
“…Several murine models of lung injury after HSCT have been established using a variety of strain combinations and conditioning regimens (Table 4). They include a lethally irradiated major histocompatibility complex (MHC)-matched, multiple minor antigen mismatch (6,20,68,172); a complete MHC mismatch model with and without cyclophosphamide (7, 69), lethally irradiated, haploidentical, parent into F1 model (20,146,147,165); a MHC class I mismatch (68,70); a MHC class II mismatch (68); and a syngeneic HSCT model using high-dose chemotherapy (71).…”
Section: The Pathogenesis Of Ips After Allogeneic Hsct Mouse Models Omentioning
confidence: 99%
“…Several murine models of lung injury after HSCT have been established using a variety of strain combinations and conditioning regimens (Table 4). They include a lethally irradiated major histocompatibility complex (MHC)-matched, multiple minor antigen mismatch (6,20,68,172); a complete MHC mismatch model with and without cyclophosphamide (7, 69), lethally irradiated, haploidentical, parent into F1 model (20,146,147,165); a MHC class I mismatch (68,70); a MHC class II mismatch (68); and a syngeneic HSCT model using high-dose chemotherapy (71).…”
Section: The Pathogenesis Of Ips After Allogeneic Hsct Mouse Models Omentioning
confidence: 99%
“…In the early phase of allo-BMT, circulating naïve donor T cells rapidly enter into the host secondary lymphoid tissues through adhesion molecule L-selectin, ␣4 integrin, ␣4␤7, MAdCAM-1, and chemokine receptor CCR5, and preventive intervention of these molecules inhibit the development of anti-host CTL and ameliorate GVHD [14 -16]. In the late phase, it has been reported that anti-host CTL infiltrate into liver via LFA-1-ICAM-1 interaction and CCR5-MIP-1␣ interaction and into the intestine via CXCR3-CXCR3 ligand interaction [17][18][19][20]. However, molecular interactions essential for the development of tissue-specific GVHD are not fully established, because severity of GVHD induced by CCR5 Ϫ/Ϫ donor cells depends on the conditioning regimen [21], and GVHD to MHC is not reduced in recipients of CXCR3 Ϫ/Ϫ donor cells [20].…”
Section: Introductionmentioning
confidence: 99%
“…14,15 The implication that MIP-1a increases the risk of immune-mediated damage to the host is supported by the observations that MIP-1a de®ciency can protect against the development of experimental autoimmune encephalitis (EAE) 16 type II collagen-induced arthritis and graft versus host disease (GVHD) in mice. 17,18 The relative in¯uence of MIP-1a on antigen-speci®c versus non-speci®c immune responses was not addressed in the studies described above.…”
Section: Introductionmentioning
confidence: 99%